2015
DOI: 10.1016/j.idairyj.2014.11.007
|View full text |Cite
|
Sign up to set email alerts
|

A survey of the main technology, biochemical and microbiological features influencing the concentration of biogenic amines of twenty Apulian and Sicilian (Southern Italy) cheeses

Abstract: a b s t r a c tTwenty Apulian and Sicilian cheeses were analysed for their concentrations of eight biogenic amines (BAs), free amino acids, pH, water activity, and subjected to microbiological characterisation. In addition, lactic acid bacteria isolated from cheeses were assayed for their capacity to generate BAs. Principal component analysis was performed to find the effect of different parameters on the distribution of the cheeses. Although short-ripened ( 30 d) cheeses did not show significant BA concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
23
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 40 publications
1
23
0
Order By: Relevance
“…Pecorino cheese production is widespread in South and Central Italy, but several regional differences are found. The raw materials are directly responsible for the characteristics of this cheese typology , while the indigenous milk microbiota might be defining for the final safety of the ripened products (Schirone et al, 2011(Schirone et al, , 2013Guarcello et al, 2015). The differences in the fermenting LAB of the several Pecorino cheeses depend strongly on the technology of transformation and on the use of a natural whey starter culture (Di Cagno et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Pecorino cheese production is widespread in South and Central Italy, but several regional differences are found. The raw materials are directly responsible for the characteristics of this cheese typology , while the indigenous milk microbiota might be defining for the final safety of the ripened products (Schirone et al, 2011(Schirone et al, , 2013Guarcello et al, 2015). The differences in the fermenting LAB of the several Pecorino cheeses depend strongly on the technology of transformation and on the use of a natural whey starter culture (Di Cagno et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…After fish, cheese is the second most frequently reported foodstuff responsible for hista-mine intoxication (12,13). A recent survey of Apulian and Sicilian cheeses revealed that about 50% of the cheeses contained at least one BA (especially histamine, followed by tyramine and putrescine) at potentially toxic concentrations (Ͼ100 mg kg Ϫ1 ) (14).…”
mentioning
confidence: 99%
“…Other lactic acid bacteria and some Gram-negative bacteria may also be responsible for the formation of BAs in cheeses (15,16). During cheese ripening, primary and secondary proteolysis releases a large amount of FAAs, some of which (e.g., Lys, Orn, His, Tyr, Trp, and Phe) are BA precursors (14,17). Therefore, the detection of bacteria possessing enzymes that convert precursor FAAs into BAs allows the risk of food intoxication to be estimated.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, in cheeses manufactured with raw milk, it seems necessary to control the factors that inhibit the ability of LAB to decarboxylate amino acids precursors of biogenic amines; being important factors the pH, the NaCl concentration, the time and the temperature of ripening between others (Komprda et al, ; Komprda, Rejchrtová, Sládková, Zemánek, & Vymlátilová, ; Linares et al, ). The controlling factors are even more crucial given that some LAB used as a dairy starter could have the ability to form amines (Guarcello et al, ).…”
Section: Resultsmentioning
confidence: 99%